Traditional Ecological Knowledge and Sustainable Mangrove Conservation: A Community-Based Perspective - Dora Boyd Cohen; Miri Pariyas Tutik Fitriya; Silviya Joshi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to identify the mangrove species utilized by the Ra’as community, determine the plant parts and utilization methods employed, examine community-based mangrove conservation practices, and explore local perceptions regarding the ecological and socio-cultural importance of mangrove ecosystems on Ra’as Island, Indonesia. Methodology: This study employed a descriptive-exploratory design using a survey method and Participatory Ethnobotanical Appraisal approach. Data were collected through field observations, semi-structured interviews, documentation, literature review, and mangrove species identification. Research tools included smartphones, field notebooks, interview guides, and taxonomic references. Data were analyzed using descriptive qualitative analysis and percentage-based quantitative analysis. Main Findings: Nine mangrove species were utilized by the Ra’as community for ecological protection, food, traditional medicine, fuelwood, handicrafts, maritime activities, and cultural beliefs. The stem was the most frequently utilized plant part, while direct use represented the dominant utilization method. Community conservation practices consisted of direct actions through mangrove planting and indirect conservation through local beliefs, social norms, and village regulations. Novelty/Originality of this study: This study integrates ethnobotanical utilization, traditional ecological knowledge, community perceptions, and conservation practices within a single analytical framework. It provides new empirical evidence from a small-island socio-ecological system in Indonesia and demonstrates how local knowledge and cultural values contribute to sustainable mangrove management and community-based conservation.